A Serological Survey of Leptospira interrogans serotype pomona in Alberta and Saskatchewan Striped Skunks and Possible Transmission Between Cattle and Skunks - Schowalter, D. B. (1981)
The range of known occurrence of Leptospira interrogans serotype pomona is extended to Alberta in striped skunks (Mephitis mephitis); no evidence of L. sejroe was found. Reacting sera from skunks were confined to the southern portion of Alberta and adjacent Saskatchewan, although a number of reactors were found sufficiently further north in Saskatchewan suggesting that a different mode of infection may be functioning there. Of 95 skunk sera from near a dairy farm infected with serotype pomona 40% were reactors. Of 438 skunk sera from other areas only 5.7% were reactors; that difference was suggestive of transmission from cattle to skunks on the dairy farm. Of 22 skunk sera collected near the dairy farm in summer none were reactors, whereas 52% of skunk sera taken the previous and following winters were. That seasonal difference was not evident among sera from other locations.